Measuring and evaluating education quality of future public administration employees at private university in the Slovak Republic - Luboš Cibák; Vojtech Kollár; Stanislav Filip (Insights into Regional Development)
The private School of Economics and Management of Public Administration in Bratislava educates experts for public administration in Slovakia through bachelor and master study programs. The high percentage of graduates employed in governing bodies and municipalities proves the high quality of theoretical and practical level of education. The scientific and pedagogical personnel and particulary the ingenious and comprehensive education quality control system has its share in achieving distinct results. The authors of this article present a well-established system of education quality. They analyze and evaluate the system of quality measuring and evaluating using internal tools and procedures. The article pays special attention to the external form of quality measurement and evaluation through independent international institution Trendence. Criteria and areas of evaluation are assessed throughout the university, Slovakia, and Europe, which is presented by more than 1,000 higher education institutions.